Development and validation of an educational video on podiatric care for the prevention of ulcers in elderly people with diabetes (Research, Society and Development, 2022)
This is a methodological study that aims to develop and validate an educational video on podiatric care for the prevention of diabetic foot in the elderly. Initially, an integrative review was carried out to support the construction of the technology, with the following research question: What podiatric care has been performed in elderly people with diabetes to prevent ulcers? After this stage, the video construction was operationalized in the pre-production, production and post-production phases. Finally, the video entitled “On the trail of prevention: a narrative about diabetes and foot care in the elderly” was developed, with a narrative in the form of a string poem and woodcut images. After production, the video content was evaluated by specialists in the field of stomatherapy, diabetes nursing care and experience in health technology development for three criteria: objectives, structure and presentation, and relevance. The content judges enabled the validation of the material with an overall Content Validity Index of 99.38% agreement. The educational technology proved to be valid in terms of content for the target audience, suggesting that in future studies the appearance and clinical validation of the video should be carried out.